Strategic Audit of Resource Utilisation and Management Efficiency in the National Economy - Shmygol, Nadiia; Bashu, Zamira; Zhagyparova, Aida; Shakharova, Aliya (Dr. Viktor Koval, 2025)
Introduction. The decisive role of strategic audits is revealed in optimising the use of national resources in the Republic of Kazakhstan and promoting sustainable economic development through detailed and systematic analysis of strategic audit processes. This involves improving resource management methods and promoting sustainable economic development through a detailed and systematic analysis of the strategic audit processes. A comprehensive analysis of strategic audits will help identify reserves for sustainable economic growth based on assessing its impact on resource use efficiency. Aim and tasks. This study evaluated the influence of strategic audit methodologies on the efficiency of national resource use in Republic of Kazakhstan. This study aims to develop and evaluate strategic audit methodologies that improve the efficiency of national resource use in the Republic of Kazakhstan and optimise resource management. Results. The study focuses on key indicators such as GDP growth, export-import ratio, and investment in technology based on secondary data. The study demonstrated the importance of these procedures for effective industrial and resource management by assessing the impact of strategic audits on resource consumption, industrial production forecasts, and gross regional product (GRP) estimates using time series, regression and correlation analyses. Correlation analysis between the volumes of industrial production and economic indicators shows a strong relationship, which is confirmed by the multiple correlation coefficient (R) of 0.989134 and the determination coefficient (R2) of 0.978386. This means that fluctuations in such key economic factors as GDP growth and technological investment can explain 97.84% of the changes in industrial production. The regression model shows statistical significance with an F-statistic of 407.3994 and a p-value of    8.37E-09, confirming its reliability and strong predictive ability in predicting the development of the Republic of Kazakhstan economy. Conclusions. This study highlights the importance of establishing and implementing a strategic audit methodology in public administration and lays the foundation for future resource management and policymaking research. A strategic audit is critical to effective resource management in the Republic of Kazakhstan and can accelerate economic growth and industrial competitiveness. Strategic audits support sustainable development by providing data for rational resource management and contribute to improved environmental sustainability.